Work Quality and Employee Productivity in Insurance Company - Joaquin, Mike Bryan A.; Urbina, Marilou C.; Pendon III, Fernando C. (International Journal of Research in Interdisciplinary Studies, 2025)
In service-oriented sectors like insurance, employee productivity is crucial to an organization's success. Productivity is highly related to operational performance and profitability, which are often evaluated by the efficiency of manpower (Smith & Wong, 2021). Quality of work, which refers to the ability to show up with accuracy, timeliness, and detail oriented, is among the top factors determining productivity. This study utilized a correlational research design wherein the researcher determined the relationship between respondents’ assessment of the insurance company employees’ level of work quality and productivity. Findings showed that the overall work quality in the insurance company is notably high across various dimensions, and the overall level of productivity in the insurance company is very high. It is also found that higher work-quality ratings are closely associated with greater productivity, emphasizing the importance of maintaining high standards of work quality to achieve better performance outcomes. The linear regression analysis concluded that work quality is a strong and significant predictor of employee productivity. The developed action plan should be utilized or implemented to ensure that insurance companies can improve their employees’ work quality and productivity. It is suggested that the managers of insurance companies should focus on further enhancing work quality as a strategy to boost overall productivity. By investing in training programs, optimizing processes, and ensuring consistent high-quality performance, the company can leverage this positive relationship to improve employee output and operational efficiency.